2017
DOI: 10.1186/s12879-017-2498-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidemiological trends in human papillomavirus infection among gynaecological outpatients in Hangzhou, China, 2011–2015

Abstract: BackgroundHPV infection is the major pathogenic factor underlying cervical cancer and precancerous lesions. The cervical HPV infection rates in gynaecological outpatients from Hangzhou, China, were studied in the period from January 2011 to December 2015.MethodsExfoliated cervical cells were harvested from gynaecological outpatients in Hangzhou from January 2011 to December 2015. Twenty-one HPV subtypes were detected using flow-through hybridization. The HPV infection rates in various disease groups were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 30 publications
9
26
1
Order By: Relevance
“…Our study found that the prevalent detection of HPV52 and HPV58 was ranked first and third among gynecological outpatients and ranked first and second among women receiving physical examinations, which deserved more attention by cancer prevention strategies. Although HPV18 is prevalent in Zhejiang and in Meizhou city of northeastern Guangdong, our study found that the prevalent detection of HPV18 was relatively low among both groups. Compared with women receiving physical examinations, the prevalent detection of HPV16, 18, 31, 33, 39, 52, 58, 68, 6, and 11 was significantly higher among gynecological outpatients ( P < .05).…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Our study found that the prevalent detection of HPV52 and HPV58 was ranked first and third among gynecological outpatients and ranked first and second among women receiving physical examinations, which deserved more attention by cancer prevention strategies. Although HPV18 is prevalent in Zhejiang and in Meizhou city of northeastern Guangdong, our study found that the prevalent detection of HPV18 was relatively low among both groups. Compared with women receiving physical examinations, the prevalent detection of HPV16, 18, 31, 33, 39, 52, 58, 68, 6, and 11 was significantly higher among gynecological outpatients ( P < .05).…”
Section: Discussioncontrasting
confidence: 66%
“…However, our result differed from the dominant HR HPV subtype distributions among gynecological outpatients reported in other regions of China. For example, in Zhejiang province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 18 . In Fujian province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations